Efficacy of pentoxifylline in the management of oral submucous fibrosis - Santosh Patil; Sneha Maheshwari (Journal of Orofacial Sciences, 2014)
Aim: Oral submucous fibrosis (OSMF) is a high risk premalignant condition predominantly seen in the Indian subcontinent. The aim of the present study was to evaluate the efficacy of newer drug pentoxifylline in the management of OSMF. Materials and Methods: A total of 106 subjects with clinic-pathologically diagnosed OSMF were included in the study and divided equally in two groups, Group A (pentoxifylline group) and Group B (placebo group). Group A was administered 400 mg pentoxifylline twice daily and Group B was given multivitamins for 3 months. Evaluation for different clinical parameters was done at regular intervals and data were analyzed using the Chi-square test. P < 0.05 was considered to be statistically significant. Results: The patients in Group A showed significant improvement (P < 0.05) in all the parameters measured, mouth opening, tongue protrusion, pain associated with the condition, burning sensation and difficulty in speech and swallowing. However, few patients from Group A complained of bloating, nausea, anxiety and dyspepsia. Conclusion: Pentoxifylline can bring about significant clinical improvements in the symptoms like mouth opening and tongue protrusion, thereby improving the quality of life of the affected individuals.